Udspring og fald - Gammelgaard, Lasse (Passage - Tidsskrift for litteratur og kritik, 2012)
Lasse Gammelgaard: "Udspring og fald i Alison Bechdels grafiske erindringsværk: Fun Home. A Family Tragicomic" Abstract Lasse Gammelgaard: “Coming Out and Falling Down: Alison Bechdel’s Graphic Memoir Fun Home. A Family Tragicomic” Alison Bechdel’s Fun Home. A Family Tragicomic is a graphic memoir about the author’s own coming-out story and her father’s homosexuality and (probable) suicide. It endeavors to give an accurate account of the past, but the telling is simultaneously replete with fictionalising elements. This article probes that oscillation and describes some of the salient verbal-visual-contingent stylistic features and potentialities, which emerge as a consequence of the work’s multimodality.